Menuju Sekolah Tanpa Bullying: Program Edukasi dan Pencegahan Bullying pada Siswa Sekolah Dasar - Nursia Nursia; Erick Karunia; Muh.Irfandy Azis; Roni Padliansyah; Rahmi Nur Islami; Deni Marsha; Aswan Aswan; Nurjannatul Hasanah; Widyastuti Cahyaningrum; Indah Sari; Muhammad Syahril (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This Community Service (PKM) activity aimed to create a bullying-free school environment at SDN Utama 2 Tarakan by enhancing students' knowledge and awareness. The program, executed in November 2025, employed an participatory-educational approach that included needs analysis, preparation of interactive materials (visuals and videos), execution of socialization, and roleplay simulations designed to foster empathy and courage among students. The results indicate that the interactive and relevant educational program successfully led to a significant increase in understanding of bullying categories and consequences among elementary school students, along with success in cultivating their commitment to becoming active upstanders. Furthermore, dedicated mentoring effectively strengthened the teachers' role in early detection. Overall, the program successfully instilled anti-bullying values, and it is recommended that the school internalize these materials periodically and establish an anti-bullying task force to ensure the sustained positive impact within the school environment.